Erythropoietin secretion during hypobaric hypoxia. Modulation of the response by the level of erythropoiesis - E. Bozzini, Carlos (Acta Andina, 2025)
Erythropoietin (EPO) is a glycoprotein hormone that is part of a feedback mechanism involved in the control of red cell production. Plasma EPO levels (PEPO) of mammals are related to the oxygen (02) supply to tissues relative to their 02 needs. However, clinical and experimental observations indicate that factors other than 02 could be involved also in the modulation of EPO synthesis. Therefore, experimental mouse models were developed in our laboratory to investigate the possible relationship between 02 dependent EPO production and the level of erythropoiesis. Erythropoiesis was either stimulated by rh-EPO or depressed by cyclophosphamide. When mice so treated, as well as normal mice, were made hypoxemic by a 6 hour-exposure to hypobaria, pEPO was 208 % of normal and 33% of normal in mice with depressed or stimulated erythropoiesis. respectively. EPO catabolism was not affected by treatments. It is thus suggested that EPO synthesis in mammals is not only related to the 02 supply to tissues relative to their 02 needs (main stimulus) but also to the erythroid activity of the bone marrow (modulatory action).